Goalkeeper-field player in situations of offensive numerical inferiority in handball: Penalty or advantage? - Beiztegui-Casado, C.; Oliver-Coronado, J.; Sosa-González, P. I. (Revista Internacional de Medicina y Ciencias de la Actividad Física y del Deporte, 2019)
The main goal was to analyze the end resultsin offensive actions between teams that do or do not employthe goalkeeper-field playerin situations of offensive numerical inferiority in handball. The secondary objectives focus on analyzing the use and behavior of the goalkeeper-field player, as well as its role in the final offensive result and following actions in terms of the opposing team`s counterattack. 86 official match reports from the 22ndWomen's Handball World Championship (Denmark 2015) were analyzed, and the viewing, analysis and registration of the 927 situations of offensive numerical inferiority werecarried out, as well as thepertinent statistical study with SPSS v.24.The results show that the tactical or strategic use of the goalkeeper-field player favors goal scoring in situations of offensive numerical inferiority and does not punish the team which employs it, since there`s no significant difference in the probability of conceding a goalin counterattack